Adoption of formal HIV and AIDS workplace policies: An analysis of industry/sector variations - Rhoda Bakuwa (Taylor & Francis Group, 2010)
Addressing HIV and AIDS is the responsibility of many stakeholders including private sector companies. However, increasing evidence reveals that the majority of companies around the world are yet to acknowledge and respond to HIV and AIDS as a workplace issue. One factor that has been identified in the literature as playing a role in determining whether a company responds to HIV and AIDS, or not, is the industry/sector in which a company operates. This study therefore sought to empirically examine whether in the context of Malawi there were significant variations in the adoption of formal HIV and AIDS workplace policies based on the industry/sector in which a company was operating, as well as analyse the dynamics underlying such variations. Using survey data collected from 152 randomly selected private sector companies in Malawi, the results of this study revealed significant variations in the adoption of HIV and AIDS workplace policies among companies operating in various sectors. Companies in the service sector were leading the adoption compared to companies in other sectors such as the trading sector. Furthermore, the evidence from this study showed that differences in staff participation in the activities of HIV and AIDS institutions may explain the industry/sector variations. These results provide an important avenue to scale up company responses to HIV and AIDS by intensifying staff participation in the activities of HIV and AIDS institutions. Such institutions appear to play a vital role of providing up to date HIVand AIDS-related information upon which companies are able to develop a business case for responding to the epidemic.